Aplicação do método multicritério electre tri para a avaliação da maturidade de inovação de processos industriais - Lima, Nathália Cristhyna Rodrigues de (2024)
The research problem addressed consists of identifying which tools small and medium sized industries can use to monitor and control the maturity level of innovation in their processes. This work aims to develop a tool for assessing the maturity of process innovation in small and medium-sized companies in the industrial sector. The tool was designed to assist these companies in identifying and monitoring the maturity of innovation in processes, allowing a structured and systematic analysis of their practices and strategy definition. The proposed tool is developed by adopting an advanced spreadsheet in Excel, which can later be converted into a software application, facilitating its use and application by companies. The development of the tool includes the definition of key criteria and indicators that reflect the maturity in process innovation, such as organizational culture, process management, skills and strategies, tools and technologies, governance, and customers and market. The criteria are evaluated based on data collected from companies, and the results are categorized into maturity levels, allowing a clear view of how their processes incorporate innovations and what improvements are needed. The tool also incorporates pessimistic and optimistic categorization procedures of the multi-criteria decision-making method (ELECTRE TRI) to offer a more robust and comprehensive analysis. Furthermore, the research highlights the importance of Industry 4.0 technologies and the standardization of processes to leverage innovation in companies. To validate the tool, data were obtained and analyzed to identify patterns and insights into the level of maturity in innovation. The results allowed for adjusting the tool and verifying its effectiveness in different organizational contexts. The analysis of the results showed an accurate classification of alternatives into different categories of innovation, facilitating the prioritization of strategic actions and highlighting the most promising alternatives. Based on the analysis of the results obtained, specific recommendations are made to improve innovation practices and process management. This work is a significant step in helping small and medium-sized companies strengthen their innovative capabilities to achieve greater competitiveness and sustainability in the industrial sector. The use of ELECTRE TRI facilitated the prioritization of strategic actions, highlighting the most promising alternatives and enabling companies to identify areas needing improvement and areas that already show high innovative performance